Leveraging environmental stewardship mapping and assessment research as a relational process for ecology with cities - Maharramli, Bemmy Jennifer; Romolini, Michele (Frontiers in Sustainable Cities, 2023)
Increasingly, scholars, policy makers, and others have put forth that governance and management of urban environments requires a consideration of cities as social-ecological systems, necessitating involvement from a broad range of actors. Yet the research on environmental governance and development of tools to support it is often completed for rather than with those responsible for carrying out the work. We examined a university-led research effort on urban environmental stewardship in Los Angeles (LA), USA. A university urban research center conducted an environmental Stewardship Mapping and Assessment Project (STEW-MAP) in Los Angeles County, which draws upon network analysis and GIS to better understand sustainability relationships, opportunities, and gaps. STEW-MAP is intended to be both a research study examining stewardship organizations across sectors, scales, jurisdictions and geographic space, as well as an application providing tools to facilitate collaborative environmental stewardship. We sought to contribute to a better understanding of how the process of STEW-MAP can leverage sustainability for a more relational ecology with cities approach. To evaluate the process of the LA STEW-MAP, we conducted our conceptual analysis of this stewardship tool by examining co-production of knowledge and co-production of place, drawing particularly from workshops with community partners that took place in 2017 and 2018. This article will show that the LA STEW-MAP process can be improved to better operationalize a relational ecology with cities approach. This research contributes to the urban sustainability governance literature by focusing on how the process of the LA STEW-MAP can be a relational model and advance an ecology with cities' approach that captures and leverages multi-scalar interactions.